Phase angle in bioelectrical impedance analysis for assessing congestion in acute heart failure - Sangho Sohn; Jinsung Jeon; Ji Eun Lee; Soo Hyung Park; Dong Oh Kang; Eun Jin Park; Dae-In Lee; Jah Yeon Choi; Seung Young Roh; Jin Oh Na; Cheol Ung Choi; Jin Won Kim; et al. (PLoS ONE, 2025)
Background The phase angle (PhA) in bioelectrical impedance analysis (BIA) reflects the cell membrane integrity or body fluid equilibrium. We examined how the PhA aligns with previously known markers of acute heart failure (HF) and assessed its value as a screening tool. Methods PhA was measured in 50 patients with HF and 20 non-HF controls along with the edema index (EI), another BIA parameter suggestive of edema. Chest computed tomography-measured lung fluid content (LFC) was used to assess pulmonary congestion. A correlation analysis was conducted to evaluate the relationships between PhA and EI, NT-proBNP, and LFC. Receiver operating characteristic (ROC) curve analysis was used to determine the cut-off values for PhA and EI for classifying patients with HF. The area under the curve (AUC) was compared using the DeLong test to evaluate the performance of PhA and EI compared to that of LFC in correctly classifying HF. Results The PhA levels were significantly lower in the HF group. Whole-body PhA was 4.49° in the HF group and 5.68° in the control group. Moderate and significant correlation was observed between PhA measured at 50-kHz and both NT-proBNP (-0.56 to -0.27, all p-values<0.05) and LFC (-0.52 to -0.41, all p-values <0.05). The AUC for whole-body PhA was 0.827 (confidence interval [CI] 0.724–0.931, p<0.01) and was 0.883 (CI 0.806–0.961, p<0.01) for EI, and the optimal cutoffs were estimated as 5° (sensitivity 0.84, specificity 0.80) and 0.394 (sensitivity 0.78, specificity 0.95), respectively. When both PhA and EI were included in the model, the AUC increased to 0.905, and this was comparable to that of LFC (AUC = 0.913, p = 0.857). Conclusions PhA exhibited a correlation with known markers of HF and demonstrated its potential as a non-invasive screening tool for the early detection of HF exacerbation. The combined use of PhA and EI can provide a robust alternative for routine self-monitoring in patients with HF, thereby enhancing early intervention.